Korupsi Di Lingkungan Peradilan: Implikasi Terhadap Integritas Hakim Dan Marwah Penegakan Hukum Di Indonesia - Yasin, Bukhari; Tri Astuti Handayani; Irma Mangar (Universitas Pancasakti Tegal, 2026)
The public is presented with various cases that show the practice of bribery, gratuities, and buying and selling cases involving judges at various levels of the judiciary. The arrest operation carried out by the Corruption Eradication Commission against a number of judges, including within the Supreme Court of the Republic of Indonesia, indicates that the problem of corruption in the judicial realm is not an incidental case, but has a structural and cultural dimension. This research uses a normative legal research method (normative juridical) with a focus on the analysis of legal norms, principles, and concepts related to corruption in the judicial environment and its implications for the integrity of judges and the credibility of law enforcement in Indonesia. Judges who are supposed to be the guardians of substantive justice and the implementer of the rule of law have the potential to turn into transactional actors when integrity is weakened. As a result, the judicial function is no longer distorted by the law on the basis of norms and conscience, but on the basis of certain economic-political interests and forces. Further implications of this condition are the erosion of the principle of equality before the law, increasing legal uncertainty, and weakening the legitimacy of judicial institutions.